The impact of family environment on social avoidance in adolescents with depressive disorders: a chain mediation model involving basic psychological needs and core self-evaluations - Tian, Xin; Gu, Liqi; Ma, Xinrong; Zhang, Yuelan; Dang, Ling; Gou, Furong; Zhang, Mengyuan; Wang, Wenjun; Duan, Hao (Frontiers in Psychiatry, 2025)
BackgroundSocial avoidance is a critical barrier to functional recovery among adolescents with depressive disorders. Although family environment is recognized as a key contextual factor, the psychological mechanisms linking family environment to social avoidance remain unclear. This study investigated the chain mediating roles of basic psychological needs and core self-evaluations in this relationship.MethodsA cross-sectional study included 369 adolescents (12–18 years, 68.8% female) diagnosed with depressive disorders. Data were collected using the Family Environment Scale, Social Avoidance and Distress Scale, Basic Psychological Needs Scale, and Core Self-Evaluations Scale. Mediation analysis was conducted using SPSS 27.0 with PROCESS Macro Model 6.ResultsFamily environment was significantly associated with social avoidance (β = –0.4682, p < 0.001). The chain mediation model entering basic psychological needs and core self-evaluations as chain mediators accounted for 66.36% of the total effect (indirect effect = –0.3107, 95% CI [–0.3834, –0.2429]). In terms of effect‐size breakdown, the simple mediation via basic psychological needs contributed 18.37% of the total effect (β = –0.0860, 95% CI [–0.1422, –0.0367]), the simple mediation via core self-evaluations accounted for 24.90% (β = –0.1166, 95% CI [–0.1714, –0.0673]), and the chain mediation path through both mediators explained 23.07% (β = –0.1080, 95% CI [–0.1529, –0.0710]). Specifically, a more supportive family environment was strongly linked to higher basic psychological needs satisfaction (β = 0.8936, p < 0.001); basic psychological needs were then associated with core self-evaluations (β = 0.2853, p < 0.001), which in turn were related to lower social avoidance (β = –0.4238, p < 0.001).ConclusionsThis study found a chain mediation model where family environment affects basic psychological needs, which affects core self-evaluations, which in turn affects social avoidance. Based on these findings, interventions may focus on improving family communication and enhancing psychological empowerment to strengthen adolescents’ core self-evaluations and satisfaction of basic psychological needs. Accordingly, integrated family support and mental health services may help alleviate social avoidance in adolescents with depressive disorders.